2015
DOI: 10.1111/ijpp.12195
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perceptions of microneedle-mediated monitoring as an alternative to blood sampling in the monitoring of their infants

Abstract: The abbreviations section has been deleted, and the full forms of the terms mentioned therein have been incorporated in the text. Please confirm if this is okay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Microneedle sampling is another novel approach to collecting PK samples while reducing sample volume requirements and procedural discomfort. Microneedles (typically 50‐900 μm), superficially penetrate the skin to sample interstitial fluid (IF) or blood while they avoid deeper (painful) structures such as nerves . For example, a microneedle system was used to sample IF glucose in adult participants; this study showed a strong correlation between IF glucose area under the curve and plasma glucose area under the curve and could potentially be used to monitor postprandial glucose in diabetes mellitus .…”
Section: Clinical Trial Optimizationmentioning
confidence: 91%
See 1 more Smart Citation
“…Microneedle sampling is another novel approach to collecting PK samples while reducing sample volume requirements and procedural discomfort. Microneedles (typically 50‐900 μm), superficially penetrate the skin to sample interstitial fluid (IF) or blood while they avoid deeper (painful) structures such as nerves . For example, a microneedle system was used to sample IF glucose in adult participants; this study showed a strong correlation between IF glucose area under the curve and plasma glucose area under the curve and could potentially be used to monitor postprandial glucose in diabetes mellitus .…”
Section: Clinical Trial Optimizationmentioning
confidence: 91%
“…Microneedles (typically 50–900 um), superficially penetrate the skin to sample interstitial fluid (IF) or blood while avoiding deeper (painful) structures such as nerves. 43,44 For example, a microneedle system was used to sample IF glucose in adult participants; this study showed a strong correlation between IF glucose area under the curve (AUC) and plasma glucose AUC and could potentially be used to monitor postprandial glucose in diabetes. 45 In addition, the vast majority of respondents in the study did not report pain during microneedle sampling.…”
Section: Clinical Trial Optimizationmentioning
confidence: 93%
“…The group interaction promotes discussion, thus leading to a greater appreciation of older people’s views than one-to-one questioning [ 18 ]. A topic guide for focus group discussion was developed according to previous studies investigating MNs using qualitative methodologies [ 11 13 , 15 ], and then piloted to refine content and ensure validity. Each focus group began with simple introductory questions relating to medication use and common issues encountered, before progressing to the concept of MNs and discussion points on the use of such a technology by older people, as summarised in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Due to their small size and short depth of penetration, MNs provide a painless, simple, and minimally invasive way to sample skin ISF. To evaluate patient compliance with MN‐based diagnostics, Mooney et al interviewed 16 parents with experience of premature birth and the interviewees preferred MN‐mediated monitoring over traditional blood sampling in neonates 24. Based on MNs‐mediated fluid extraction strategy, Chang et al achieved offline analysis of metabolites such as glucose and cholesterol 25.…”
Section: Figurementioning
confidence: 99%